2011
DOI: 10.1097/icl.0b013e3182254caa
|View full text |Cite
|
Sign up to set email alerts
|

Comfort and Vision Scores at Insertion and Removal During 1 Month of Wear of Paragon CRT for Corneal Reshaping

Abstract: Adaptation to CRT is rapid in terms of subjective comfort and vision. Comfort significantly increases by day 5, whereas subjective vision in the morning reaches its maximum by days 15 to 21 and at the end of the day by days 10 to 15. These results are of interest to clinicians to provide evidence-based information to their patients about the expected time to adapt to CRT in terms of self-reported comfort and vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The scale has been administered for emmetropes as well as for several ocular conditions including myopic or hyperopic subjects, comparison of intraocular lenses, soft CL, CRT and Vision Quality of Life after LASIK and Overnight CL wear 9 LASIK treatments. 5,10,16,30 However, to the best of our knowledge, there are not published studies using the NEI RQL-42 questionnaire to assess the effect of the whole therapeutic options presented in this study: LASIK surgery, continuous wear of silicone-hydrogel CL, and CRT lenses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale has been administered for emmetropes as well as for several ocular conditions including myopic or hyperopic subjects, comparison of intraocular lenses, soft CL, CRT and Vision Quality of Life after LASIK and Overnight CL wear 9 LASIK treatments. 5,10,16,30 However, to the best of our knowledge, there are not published studies using the NEI RQL-42 questionnaire to assess the effect of the whole therapeutic options presented in this study: LASIK surgery, continuous wear of silicone-hydrogel CL, and CRT lenses.…”
Section: Discussionmentioning
confidence: 99%
“…Vision-related quality of life assessment tools [1][2][3][4] can be used to quantify the benefit of refractive surgery [5][6][7][8] and contact lens (CL) wear modalities, [9][10][11] including continuous wear [12][13][14] and corneal refractive therapy (CRT). [15][16][17] In the last decade, the vision care professional community has increased their interest in developing appropriate quality of live instruments to assess the benefits to choose one or another therapeutic alternative for the correction of refractive error. 1,5,[18][19][20][21] To test the vision-related quality of life, specifically developed and validated psychometric questionnaires are requiered.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have reported that RGP lenses worn overnight during orthokeratology treatment are well tolerated by children, 13,14,29 which is probably related to the fast adaptation to this modality. 30 Children also have been shown to successfully adapt to RGP lenses on a daily wear basis in different clinical trials. 19,31 This makes RGP lenses a viable option for controlling myopia progression even if they have to be worn on a daily wear basis.…”
Section: Discussionmentioning
confidence: 99%
“…BCLCVA and VAS score were measured a week later at the first visit of patients. VAS is previously used to rate comfort with contact lenses [ 14 , 17 ]. VAS were administered by asking patients to record their subjective impressions of vision and comfort using a scale from 0 (lowest) to 10 (highest).…”
Section: Methodsmentioning
confidence: 99%